Théâtre de Collège: Une Interdépendance Précaire en Acadie - Perron, Judith C. (Theatre Research in Canada / Recherches théâtrales au Canada, 1991)
College theatre is one historic form of theatrical activity that is rarely mentioned these days in French-speaking Acadia. Yet its profile was once elevated, and indeed its early success gave rise to a first generation of Acadian playwrights. The very nature of college theatre, with its highly specific parameters of composition and production, appears to explain the lack of historical importance which is otherwise generally ascribed to the appearance of a new genre in a nation’s literary history. Il est une activité théâtrale importante dont on ne parle presque plus aujourd’hui en Acadie. Le théâtre de collège a en effet connu un moment de gloire certain, et son succès a fait naître une première génération de dramaturges acadiens. Cependant, vu son mode de production et sa nature pragmatique particulière, on s’étonne peu que ce théâtre ne revête pas l’importance historique qu’on accorde généralement àl’apparition d’un nouveau genre dans la littérature d’une nation.